Genetic evidence supports a role for the yeast CCR4-NOT complex in transcriptional elongation. - Denis, C L (2001)
The CCR4-NOT complex is involved in the regulation of gene expression both positively and negatively. The repressive effects of the complex appear to result in part from restricting TBP access to noncanonical TATAA binding sites presumably through interaction with multiple TAF proteins. We provide here genetic evidence that the CCR4-NOT complex also plays a role in transcriptional elongation. First, defects in CCR4-NOT components as well as overexpression of the NOT4 gene elicited 6-azauracil (6AU) and mycophenolic acid sensitivities, hallmarks of transcriptional elongation defects. A number of other transcription initiation factors known to interact with the CCR4-NOT complex did not elicit these phenotypes nor did defects in factors that reduced mRNA degradation and hence the recycling of NTPs. Second, deletion of ccr4 resulted in severe synthetic effects with mutations or deletions in the known elongation factors RPB2, TFIIS, and SPT16. Third, the ccr4 deletion displayed allele-specific interactions with rpb1 alleles that are thought to be important in the control of elongation. Finally, we found that a ccr4 deletion as well as overexpression of the NOT1 gene specifically suppressed the cold-sensitive phenotype associated with the spt5-242 allele. The only other known suppressors of this spt5-242 allele are factors involved in slowing transcriptional elongation. These genetic results are consistent with the model that the CCR4-NOT complex, in addition to its known effects on initiation, plays a role in aiding the elongation process.